DEVELOPING READING SKILLS USING SIGHT WORD READING STRATEGY THROUGH INTERACTIVE MOBILE GAME-BASED LEARNING FOR DYSLEXIC CHILDREN - Marcella, Peter (Universiti Malaysia Sarawak (UNIMAS), 2015)
Dyslexia is a referring term for learning disabilities within reading, writing and spelling. Children with dyslexia use all of their senses to interact with their surroundings. They are easily attracted to pictures rather than words and are highly imaginative. There are various approaches to develop a reading success for dyslexic children including repeated reading, sight word drills, development of vocabulary and semantics, and increase speed of processing letter and syllable pattern. Sight words provide an excellent foundation for reading as the higher frequency of child see the word the more they able to recognize and understand the meaning of the word as a whole. These days, many applications for mobile devices have been developed to assist children with dyslexia in their learning. In fact, children with dyslexia are more attracted to these kind of technology compared to the traditional one. Therefore, a solution is proposed to help them in reading by developing an interactive mobile game-based application. This application is designed to improve their reading skills using sight words reading strategy applied in short story, rhyme and song lyric. The application is called as "Mr Read". The goal of this application is to help dyslexic children to gain their learning spirit and improve their vocabulary as part of their reading development. Sight word strategy is used in a fun context through different reading platforms and interesting game. A test has been conducted at Dyslexia Association of Sarawak, involving teachers and students. Teachers and students were given a tablet to play the Mr Read application. The results have shown positive feedbacks on Mr Read's method of learning.